Peranan Standardisasi Pengemas dalam Rangka Menunjang Pengembangan Industri Makanan, Minuman Dan Rokok - D Karyadi (Balai Besar Kimia dan Kemasan, 1983)
Package is very important for foods, beverages and cigarrettes. Food is very sensitive to environmental effect, therefore they must be protected with the packaging. One of the requirements of the packaging material for food is not interaction between food and packaging material or vice versa. The packaging material which is usually used, consist of : glass, metal, plastic, paper, boxes and Aluminium foil. In generally the function of the packaging is as container for easily to storage, transportation and distribution. The other function is to protect, to preserve and to promote the product. With the development of food, beverage and cigarrette industry, it means that the needs of package is increased.